THE CONTEXTUALIZATION OF THE TRADITIONAL ISLAMIC BOOK ON CONTEMPORARY ISSUES - Safriadi, Safriadi (Hunafa: Jurnal Studia Islamika, 2021)
This research is a research library, and belongs to qualitative research. The research approach is used with a normative approach. The results reveal that the role of the traditional islamic book is still very important and contextual. The use of analogy and comparative methods is applied in determining law, both state and religion. Looking for common ground then concocting through long dialectics. The orientation is to apply religious law without touching or even changing plural local wisdom, either in the order of customary law or national law. The contextualization of the traditional islamic book here is a form of effort to maintain human social relations, as well as to eliminate the rigid paradigm in understanding the traditional islamic book and in its application. Money laundry in the view of the traditional islamic book is prohibited because of the correlation with the use of booty.